Identification Arbuscular Mycorrhiza Fungi (Amf) Legume Plant On Microscopik Consevation Tillage Cropping Season To 29 - Sari, Sismita; Kumastuti, Any; Indrawati, Wiwik (Jurnal Penelitian Pertanian Terapan, 2017)
Arbuscular Mycorrhiza Fungi (AMF) is a form of  mutualistic symbiosis between fungi and plant roots. FMA existence in  soil is influenced by several agricultural activities such as tilling and fertilizing. The purpose of this study (1) Obtaining  data on the number of FMA in each treatment and conservation tillage . (2) Knowing  the types FMA in each treatment and conservation tillage planting season  to 29. The study was a randomized block design (RAK) , arranged as factorial (2x3), with three replications. The first factor is the intensive tillage (T1), no-tillage (Zero Tillage) (T2) Minimum tillage (Minimum Tillage), and  Land Intensive (Full Tillage) (T3); and the second factor is without fertilizer N (N0) and fertilizer application of 100 kg N ha-1 (N1), and  Fertilizer of 200 kg N ha-1 (N2). The method used in this study is a description method by observation techniques, the method used for the isolation of spores of strain engineering castings and followed by centrifugation. Observations were made using a microscope binoculars and digital camera, the spores are observed then grouped based on their morphological characters, identification of mycorrhizal done using a guide book "Working with mycorrhizas in Forestry and Agriculture" and reaffirmed by using INVAM website.  Based on results  of research and discussion can be concluded. The number of spores in the soil no tillage without nitrogen doses is 1,333 at doses 100 kg N spore number is 1,253, and as high as 1,648 spores at dose of 200 kg N. The number of spores on minimum tillage  200 kg of nitrogen dose was 271, on 100 kg dose was 520 spores, and without nitrogen fertilizer contained spores 780. at most that  intensive tillage highest number of spores on spore number without nitrogen fertilizer is 4.078, and the number of spores 1,124 at the dose of 100 kg nitrogen, 941 the number of spores nitrogen dose of 200 kg. There are four genera of spores discovered in minimum tillage with various doses Nitrogen fertilizer is the genus Glomus, Acaulospora, Gigaspora, and Scutelospora. Genus most obtained is Glomus and Acaulospora. Type spores were found from 4 genera dominated by genus Glomus with a variety of different types.